THE EFFECT OF EMOTIONAL COMPETENCE ON CUSTOMER LOYALTY WITH CUSTOMER EXPERIENCE AS A MEDIATOR (CASE STUDY AT BANK SULTRA KANTOR FUNGSIONAL UHO) - Azis Muthalib, Dzulfikri (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
This study aims to examine and analyze the effect of emotional competence on customer loyalty mediated by customer experience at Bank Sultra Kantor Fungsional UHO. The population in this study consists of all customers of Bank Sultra Kantor Fungsional UHO. The sample includes 85 customers selected from this population. This study employs Partial Least Squares (PLS) analysis. The results indicate that emotional competence has a positive and significant effect on customer experience at Bank Sultra Kantor Fungsional UHO. Emotional competence also has a positive and significant effect on customer loyalty at Bank Sultra Kantor Fungsional UHO. Furthermore, customer experience has a positive and significant effect on customer loyalty at Bank Sultra Kantor Fungsional UHO. Finally, customer experience is proven to mediate the effect of emotional competence on customer loyalty at Bank Sultra Kantor Fungsional UHO.